Quantitative safety assessment for reactor size variation on high pressure methanol production / Mohd Aizad Ahmad, Anis Adila Rozman and Zulkifli Abdul Rashid - Ahmad, Mohd Aizad; Rozman, Anis Adila; Abdul Rashid, Zulkifli (Universiti Teknologi MARA Shah Alam, 2023)
This work studied carbon capture utilization (CCU) to methanol synthesis, which analyses reactor size's impact on high-pressure methanol production. As high pressure poses a high probability of process vessel leakage, assessment on its potential hazardous chemical impact such as toxicity, fire, and explosion must be conducted. This study examines how reactor size affects high-pressure methanol plant accident scenarios due to different leakage sizes of reactors and at various day and night conditions. HYSYS was used in this investigation to identify significant chemical components at high pressures. The analysis only limited to four hazardous chemical components namely methanol, carbon dioxide, carbon monoxide, and hydrogen. Then, ALOHA specifies the principal chemical component for the worst-case accident scenario. MARPLOT was used to quantify the methanol plant's safety by utilising distance and area plot threat analysis for reactor size variation. The volume of the reactor used is 42, 20, and 5 m 3, with pressure conditions of 76, 184, and 331 bar, as the 10 mm, 75 mm, and 160 mm leakage size of the reactor has been simulated. The simulation in ALOHA was done by considering day and night conditions with one dominant wind direction according to the plant's location. The results show that the highest people affected incident was due to the toxic release of methanol from a 160 mm leak size during the night in Modified Plant 2. This scenario resulted in a percentage people affected for night conditions of 56.53%. This study is useful to predict worst-case people affected with variation for reactor size on high-pressure conditions.